2018
DOI: 10.7196/samj.2018.v108i3.12661
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal perspective on violence in the lives of South African children from the Birth to Twenty Plus cohort study in Johannesburg-Soweto

Abstract: Background.Violence against children is a significant cause of personal suffering and long-term ill health, poor psychological adjustment, and a range of social difficulties, including adverse effects intergenerationally. Objectives. Using a large corpus of longitudinal data collected in the Birth to Twenty Plus cohort, to give an overview of exposure to and experience of violence, as well as perpetration of violence, across childhood, reported contemporaneously by several informants. This overcomes limitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 23 publications
3
29
0
Order By: Relevance
“… 46 This risk of early sexual abuse amongst boys has also been shown in longitudinal research in South Africa to start early. 47 Thus, intervention such as Amagugu, which encourage communication with boy children about the risk of sexual abuse, has important potential beyond the context of HIV.…”
Section: Discussionmentioning
confidence: 99%
“… 46 This risk of early sexual abuse amongst boys has also been shown in longitudinal research in South Africa to start early. 47 Thus, intervention such as Amagugu, which encourage communication with boy children about the risk of sexual abuse, has important potential beyond the context of HIV.…”
Section: Discussionmentioning
confidence: 99%
“…One participant indicated that the man who raped him was a serial killer who is well known in the community, while another man stated that the young man who raped him had recently returned from jail. South African men, women and children face the dual burden of rape and murder as a crime daily [ 59 – 61 ]. The fear of being killed was also reported as a barrier for not reporting rape to police where participants reported that they feared reporting rape to the police because the rapist had threatened to kill them if they attempt to report the rape to the police.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the study of other social phenomena, methodological issues also accompany the study of missing children. As with the wider literature on violence against children, there is an apparent lack of 'systematic research into the scale and forms of violence experienced by children' (Richter et al 2018) which extends beyond statistics. Sources of data used in this article include, firstly, interviews from a larger study about human trafficking for sexual exploitation in South Africa (Van der Watt 2018) in which 120 multidisciplinary participants from the criminal justice system, NGOs, the sex trade and victims of human trafficking shared their lived experiences.…”
Section: Methodsmentioning
confidence: 99%
“…However, the authors were not able to ascertain at the time of the writing the reasons why this may be so in the South African context. The literature on violence against children in South Africa has repeatedly shown that African children bear the brunt of violent acts and abuse committed against them whether by family, community members, strangers or their peers (Hsiao et al 2018;Mathews & Benevuti 2014;Optimus Study 2016;Richter et al 2018). Below is a breakdown of the racial distribution of children reported to Missing Children SA: Surprisingly, 'white' or Caucasian children make up the majority of children reported missing.…”
Section: The Scope Nature and Extent Of Missing Children In South Afmentioning
confidence: 99%